Propriedade industrial e defesa da concorrência: experiências estrangeira e brasileira e análise principiológica - Falcone, Bruno (2012)
In the era of knowledge, by triggering a real technology race by the various economic agents, the industrial property, more than an exclusive right, consists in a powerful instrument of competition. Unfortunately, such a facet of industrial property has never been exploited and disseminated either by the local legal community or national companies. The first one preferred to adopt a position characterized by a strong social appeal (not always technically grounded) and the second ones did not do so because they simply lacked a culture of protection of their intangible assets. A simplistic and perfunctory judgment of the matter may suggest that industrial property and competition law are two areas of Law completely antagonistic and irreconcilable with each other. Such a construction could jeopardize the legal safety that economic agents need to invest in scientific development and technology research. This study therefore aims at examining, in a scientific fashion, the relationship between industrial property law and competition law. First and foremost, an assessment of both foreign and Brazilian experiences will be conducted as a preparatory field for a principiologic analysis of both areas of Law. Once the relevant principles are identified in both foreign and Brazilian experiences according to the deductive method, it will be investigated which principles are either coincident or harmonic and the theoretical formulation of Robert Alexy will be applied to cases of conflict, in order to demonstrate that the relationship between both legal areas is actually harmonic and complementary